Supporting adolescent athletes' dual careers: The role of an athlete's social support network. (September 2018) - Knight, Camilla J.; Harwood, Chris G.; Sellars, Paul A.
Abstract: Objectives: The objectives of this study were to, (a) understand the role of the social support network in facilitating adolescent athletes' dual careers in sport and education, and; (b) gain insights into the factors that may optimize the provision of such support. Design: A two-stage qualitative study. Method: In stage one, four different sport and education settings in the UK were examined: A tennis academy, a football academy, a national field hockey squad, and a high-performance swimming squad. Interviews were conducted with two athletes and associated significant others from each setting. In stage two, nine current or former international athletes from a variety of sports and countries recalled their experiences of managing a dual career. Analysis was conducted following the procedures outlined by Miles, Huberman, and Saldaña (2014). Results: Overall, athletes in stage one and two perceived that to maintain their dual careers, they were heavily dependent upon the support of significant others. The role of the support network was to recognize the demands of a dual career, anticipate problems, value education, minimize barriers, and create autonomy-supportive environments. Key factors to optimize such support were focusing on the whole person, providing integrated support, and fostering a culture that promotes continuing education. Conclusions: Results indicate that athletes require particular types of support within their home, at school, and in their sport context to be able to manage their dual career. However, a range of individual and group-level factors may influence the extent to which such support is available to athletes. Highlights: Examines the role of athletes' support network in facilitating a dual career. Two-stage qualitative study combining interviews from current and former athletes. Role of support network is to recognize athletes' needs, anticipate problems, remove barriers, and value education. It is also beneficial if the support network create an autonomy-supportive environment. Factors that facilitate support include focusing on the whole person and integrated efforts across the network.